Implementasi Pendidikan Berbasis Multikultural sebagai Upaya Penguatan Nilai Karakter pada Siswa SMA Negeri 1 Pamekasan - Agung Suprianto; Syaiful Syaiful (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2021)
Abstract The problem of diversity requires a special strategy to solve, one of which is through education. In this regard, multicultural education offers an alternative through the application of educational strategies and concepts based on the utilization of diversity in society. The purpose of this study is to describe the implementation of multicultural-based education as an effort to strengthen the character values ​​of SMA Negeri 1 Pamekasan students. Describe the supporting and inhibiting factors for the implementation of multicultural-based education in SMA Negeri 1 Pamekasan students. The results showed that the implementation of multicultural education at SMA Negeri 1 Pamekasan was carried out by integrating multicultural values ​​into the subjects of Religious Education, Citizenship Education, and Social Sciences as well as the inculcation of values ​​in their learning activities. Second, integration into programmed self-development activities, namely through extracurricular activities, habituation, spontaneous activities and exemplary activities. The supporting factors for the implementation of multicultural-based education at SMA Negeri 1 Pamekasan are school climate, school curriculum, facilities and infrastructure, the role of teachers, school programs and activities. Meanwhile, the inhibiting factor is the adherence to the principles of the Madurese community, namely